Slow Epidemic of Lymphogranuloma Venereum L2b Strain - Spaargaren, Joke (Centers for Disease Control and Prevention, 2005)
We traced the Chlamydia trachomatis L2b variant in Amsterdam and San Francisco. All recent lymphogranuloma venereum cases in Amsterdam were caused by the L2b variant. This variant was also present in the 1980s in San Francisco. Thus, the current "outbreak" is most likely a slowly evolving epidemic.